Pengaruh Kompensasi, Motivasi, dan Kompetensi SDM Terhadap Kinerja Karyawan: Studi Kasus pada UMKM Griya Tas Indah Sidoarjo - Raytasayah, Zeinnisa Inggit; Bowo Santoso (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to explain the effect of compensation, motivation, and HR competence on employee performance. The object used in this research is the employees of UMKM Griya Tas Indah Sidoarjo. While the sample in this study were employees of UMKM Griya Tas Indah Sidoarjo. The sampling method used was saturated sampling technique with a total of 35 respondents. Data analysis in this study was carried out using the Partial Least Square (PLS) method which shows that all of these tests used a quantitative research design, data analysis in the form of descriptive statistics and PLS analysis. Based on the research results, it can be seen that: 1) the fulfillment variable is able to support employee performance improvement, 2) motivational variable is able to support employee performance improvement, 3) HR competence variable is able to support employee performance improvement.